Nagelamide I and 2,2'-didebromonagelamide B, new dimeric bromopyrrole-imidazole alkaloids from a marine sponge Agelas sp - Iwai, Takahiro; Kubota, Takaaki; Fromont, Jane; Kobayashi, Jun'ichi (Chemical & pharmaceutical bulletin, 2014)
New dimeric bromopyrrole-imidazole alkaloids, nagelamide I (1) and 2,2'-didebromonagelamide B (2), have been isolated from an Okinawan marine sponge Agelas species. The structures of 1 and 2 were elucidated based on analyses of the spectral data. Nagelamide I (1) was the first symmetric dimeric bromopyrrole-imidazole alkaloid consisting of two subunits connected with a single bond.